Can LED lights replace lasers for detailed investigations of boiling phenomena?. (February 2021) - Kossolapov, A.; Phillips, B.; Bucci, M.
Highlights: Simple, safe and affordable LED technique to track dry and wet areas and microlayer Demonstration in flow boiling at ambient and high-pressure conditions Combination with infrared thermometry to study heat flux partitioning Abstract: Capturing the dynamics of the triple contact line at the base of a vapor bubble is crucial to the development and validation of boiling heat transfer and boiling crisis models. To this end, laser-based techniques are the state-of-the-art. However, they have technical limitations, e.g., due to the presence of parasite interference patterns or laser speckle, and are often complicated to implement and operate. In this paper, we propose and discuss the rationale of alternative phase detection techniques based on LED lights. Colored LED lights have a coherence length of several micrometers, which is long enough to create interference patterns when reflected by the microlayer and short enough to prevent the formation of the parasite interference patterns caused by lasers. We show that, even with a simple optical setup, these LED-based techniques can create images of superior quality and uniformity, making it possible to resolve smaller boiling features, e.g., size and shape of bubble footprint at high-pressure conditions. Moreover, LED lights are much less expensive, safer, and easier to operate than lasers, which is an obvious advantage for researchers that want to either enter the field or expand their measurement capabilities. We demonstrate the use and the potential of these LED-based techniques with experimental results obtained in subcooled flow boiling of water, at both ambient and high-pressure conditions. We also demonstrate how this technique can be combined with infrared thermometry to study the formation and evaporation of the microlayer, other heat transfer mechanisms associated with the growth and departure of a vapor bubble, and the heat flux partitioning over the entire boiling surface.